(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research deals with the foreign political relations of the state of Tripoli-Gharb during the rule of Youssef Pasha al-Qaramanli, which extended between the years 1795 - 1832 AD, with various neighboring Ottoman states such as Tunisia and Egypt, and with European countries and the United States of America. The location of Tripoli-Gharb in the middle of the Mediterranean Sea on its southern bank contributed to Tripoli of the West played an influential role in maritime navigation and international trade in the Mediterranean, especially at that important stage in which the military activity of the fleets of the North African states (Tunisia, Algeria, Tripoli of the West) increased, as the fleets of those Ottoman states were attacking European ships and controlling them. Therefore, various European countries, and later the United States of America, sought to win the favor of the governments of those states, led by the government of Youssef Pasha al-Qarmanli in Tripoli, the West, by concluding treaties and agreements to guarantee the freedom of navigation of their ships in the Mediterranean without exposing them to attacks by ships belonging to Tripoli, the West. In addition, the governments of some of those countries sought to Especially France and Britain are behind those treaties to exploit Libya’s strategic location leading to the heart of the African continent with the aim of expansion and control. Therefore, it can be said that the political conditions and maritime conflicts in the Mediterranean contributed to the establishment of active foreign political relations for Tripoli in the West during the reign of Youssef Pasha Al-Qarmanli, with various countries with interests. Political and commercial vitality in the Mediterranean.